COVID-19 Infections and Inflammatory Markers in Patients Hospitalized During the First Year of the Pandemic - Parkavi Kalaiselvan; Pitchaporn Yingchoncharoen; Jerapas Thongpiya; Arunee Motes; Kenneth Nugent (Journal of Primary Care & Community Health, 2023)
Background: The clinical presentations in patients with SARS-CoV-2 (COVID-19) infections range from asymptomatic upper respiratory infections to acute respiratory failure with bilateral pulmonary infiltrates requiring mechanical ventilation. Clinicians often measured inflammatory markers in hospitalized patients to characterize the severity of the infection. Multiple studies published in 2020 reported information on the frequency of elevated inflammatory markers in hospitalized patients in various categories of disease severity. Methods: The PubMed database was searched using the terms “Inflammatory markers in COVID-19 patients” and “Clinical features of patients infected with COVID-19.” Thirty-three publications were analyzed in detail to determine which inflammatory markers were increased and the frequency of these increases in various clinical classifications, including patients requiring hospitalization, patients with pneumonia, patients with severe infection, patients requiring intensive care unit admission, and patients who died. Results: C-reactive protein (CRP) was the most frequently elevated inflammatory marker in all categories. Ferritin, D-dimer, and erythrocyte sedimentation rate levels were also frequently elevated. In general, frequencies were higher in patients with more severe infections. For example, 24 out of 24 patients who died had an elevated CRP level. Conclusion: This review provides concrete information about the frequency of various inflammatory markers in patients with COVID-19 infection who required hospitalization. It also provides us some insight into the approach clinicians took in the early phase of this pandemic in their efforts to characterize these patients and perhaps understand the disease process better. However, these results might suggest that clinicians and laboratory directors should develop protocols to optimize laboratory testing.